Multivalent, Bispecific αB7-H3-αCD3 Chemically Self-Assembled Nanorings Direct Potent T-cell Responses Against Medulloblastoma - Mews, Ellie A.; Beckmann, Pauline J.; Patchava, Mahathi; Wang, Yiao; Largaespada, David A.; Wagner, Carston R. (bioRxiv, 2022)
Few therapeutic options have been made available for treating central nervous system tumors, especially upon recurrence. Recurrent medulloblastoma is uniformly lethal with no approved therapies. Recent preclinical studies have shown promising results for eradicating various solid tumors by targeting the overexpressed immune checkpoint molecule, B7-H3. However, due to several therapy-related toxicities and reports of tumor escape, the full potential of targeting this pan-cancer antigen has yet to be realized. Here, we designed and characterized bispecific chemically self-assembling nanorings (CSANs) that target the T cell receptor, CD3ε, and tumor associated antigen, B7-H3, derived from the humanized 8H9 single chain variable fragment (scFv). We show that the αB7-H3-αCD3 CSANs increase T cell infiltration and facilitate selective cytotoxicity of B7-H3+ medulloblastoma spheroids and that activity is independent of target cell MHC class I expression. Importantly, non-specific T cell activation against the ONS 2303 medulloblastoma cell line can be reduced by tuning the valency of the αCD3 targeted monomer in the oligomerized CSAN. Intraperitoneal injections of αB7-H3-αCD3 bispecific CSANs were found to effectively cross the blood-tumor barrier into the brain and elicit significant anti-tumor T cell activity intracranially as well as systemically in an orthotopic medulloblastoma model. Moreover, following treatment with αB7-H3-αCD3 CSANs, intratumoral CD4+ and CD8+ T cells were found to primarily have a central memory phenotype that displayed significant levels of characteristic activation markers. Collectively, these results demonstrate the ability of our multi-valent, bispecific CSANs to direct potent anti-tumor T cell responses and indicate its potential utility as an alternative or complementary therapy for immune cell targeting of B7-H3+ brain tumors. This study presents αB7-H3-αCD3 bispecific CSANs as a promising, new immunotherapeutic option for patients with established B7-H3+ medulloblastomas.